Draft Seventh Five Year Plan (1985-90) and Annual Plan (1985-86) Government of Rajasthan - Planning Commission (Planning Commission, 1985)
Stretching over an area of 3.4,2 lakh Sq. Kms. Rajasthan is the second largest country accounting for nearly ten percent of its area of this. 55 percent covering 1.98 lakh sq.kms. and inhabited by about one-third of the State's population lies in the heart of the great Indian desert, the that, forming a geographical region of chronic under development and an easy prey to drought and scarcity. The constraints imposed by years of backwardness and geographical disadvantages have left the State far behind in the race for economic development.
Government of Rajasthan
Government of Rajasthan